PENGARUH PERAN GABUNGAN KELOMPOK TANI TERHADAP PENINGKATAN PRODUKTIVITAS USAHATANI KUBIS ( Brassica oleracea ) - suswadi; sutarno; Kusriani Prasetyowati; Agung Riyanto (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2021)
This study aims to determine the effect of each variable of the Gapoktan cooperation system on the productivity variable of Cabbage farming. And to analyze the coefficient of determination which serves to determine the magnitude of the influence of the independent variable on the dependent variable. This research was conducted at Gapoktan in Bandungrejo Village, Ngablak District, Magelang Regency. The method of determining the location used a purposive method and the sampling method was carried out by the Random Sampling method with the number of respondents as many as 30 cabbage farmers. The results showed that the linear regression analysis showed that the effect of the effectiveness of the Gapoktan cooperation system on increasing farm productivity had a significant effect. The effectiveness of the Gapoktan cooperation system has a positive effect on-farm productivity. The effect of the effectiveness of the cooperation system in increasing farm productivity is 22.8%. The remaining 77.2% is influenced by other variables. So that the effectiveness of the cooperative system in increasing productivity has a low relationship.